(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The reflectivity spectra of ZnTe and Zn0.97Yb0.03Te single crystals were obtained in the 2 - 6eV photon energy range at room temperature. The introduction of Yb affects the band structure of ZnTe material. Its provides to the spectra revealed distinct structures at energies of E1, E1+ and E2 critical points and to the remarkable blurring of the maximum E2, and to the disappearance of the maxima e1 and . The observed changes in the shapes of the spectra, caused by the presence of ytterbium Yb, have been compared with the calculated band structure of binary compound ZnTe available in the literature. The intra-atomic transitions, due to ytterbium introduced as an impurity to the ZnTe crystal, in the Zn0.97Yb0.03Te material were also discussed. تم قياس أطياف الانعكاسية للبلورتين ZnTe و Zn0.97Yb0.03Te في مجال الطاقة من 2 إلى 6eV في درجة حرارة الغرفة. إن إدخال الايتيربيوم Yb أثر على البنية القطاعية للمادة ZnTe. مما أدى إلى أن الأطياف أظهرت بنيات جلية عند طاقات النقط الحرجة E1 و E1+ كما أدى إلى تعرض القمة E2 واختفاء القمتين e1 و. إن التغيرات الملاحظة في أشكال الأطياف، بسبب وجود الايتيربيوم Yb، تم مقارنتها مع البنية القطاعية المحسوبة للمركب الثنائي ZnTe المتوفرة في المراجع. نوقشت أيضاً الانتقالات الذرية الداخلية، نتيجة إدخال الايتيربيوم كإشابة إلى البلورة ZnTe، في المادة Zn0.97Yb0.03Te.